Detached self-observation as a developmental catalyst: theoretical insights from dynamical systems thinking, cultural mediation, and contemplative practice - Loncar, Lea; Fiskum, Charlotte (Frontiers in Psychology, 2025)
Detached self-observation, a central dimension of mindfulness meditation, has emerged as a key metacognitive and emotional-regulatory capacity across psychology, education, and neuroscience. This theoretical paper proposes meditation as a developmental catalyst, drawing on contemporary scholarship. Detached observation is reframed here as a culturally mediated competence grounded in both phenomenological embodiment and symbolic internalization. Drawing on recent research in contemplative neuroscience, cultural psychology, dynamical systems theory, and virtue ethics, the paper explores how practices of self-observation foster cognitive-affective flexibility, reflective wisdom, and prosocial behavior. Crucially, the paper also considers potential contraindications, including the risk of depersonalization and cultural misalignment, highlighting the importance of context-sensitive application. Meditation is proposed as a dynamic developmental catalyst, with implications for personal transformation and collective well-being. The paper integrates cultural mediation theory, embodied phenomenology, and transpersonal and dynamical systems perspectives on psychological development. Implications are outlined for educational, therapeutic, and civic contexts across diverse contemplative practices.